Radionuclide teranostic of malignancies - V. I. Chernov; O. D. Bragina; I. G. Sinilkin; A. A. Medvedeva; R. V. Zel’chan (Вестник рентгенологии и радиологии, 2016)
This review shows some basic information regarding the relatively new and one of the promising areas, called "theranostics" and also discusses its basic principles. Special attention is paid to the study of approaches in selecting the most appropriate in the application of radioisotopes for solutions appropriate diagnostic and therapeutic applications. Also presented the main directions in the work with monoclonal antibodies and their use in radionuclide theranostics.